2011
DOI: 10.1007/s12013-011-9265-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of a Dendritic Cell Vaccine Raised Against Heat-Shocked Glioblastoma

Abstract: Establishment of a detection platform for glioblastoma-dendritic cell (DC) vaccine preparation and to determine the efficacy of the vaccine in a clinical trial. Autologous glioblastoma-DC vaccine was prepared from a glioblast specimen procured from surgical resection. The specimen was used to enrich the vaccine with peripherally blood-derived DCs after heat-shock induced, glioblastoma apoptosis. The control group received conventional treatment of surgery and radio-chemotherapy post-operation. The therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 23 publications
(26 reference statements)
2
63
0
Order By: Relevance
“…The majority of vaccinations were started within 1 week to 3 months after resection. 3,4,16,32 However, previous reports did not describe the time of initiation of vaccination in detail. 4 In our study, 5 of 6 patients with glioblastoma had PD at the end of the first session of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of vaccinations were started within 1 week to 3 months after resection. 3,4,16,32 However, previous reports did not describe the time of initiation of vaccination in detail. 4 In our study, 5 of 6 patients with glioblastoma had PD at the end of the first session of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Phase I and II studies demonstrated the safety and efficacy of DC vaccination against malignant gliomas. 5,16,36 Vaccination with DCs was also studied in 313 patients with high-grade gliomas. 44 The antigen sources were tumor lysate, peptides eluted from autologous tumor cells, defined peptides, and autologous tumor cells.…”
mentioning
confidence: 99%
“…Significantly, adverse events were limited to transient elevations in liver transaminases with no secondary autoimmune disease [3943]. In a similar trial with 25 randomized patients, DC vaccination with heat shocked autologous tumor lysate delayed tumor recurrence compared to a control cohort, increased levels of peripheral T cells (CD3 + , CD4 + , CD8 + ), and NK cells, and restored CD4:CD8 ratios [44]. Response of peripheral lymphocytes to cytokine stimulation via pSTAT signaling was later identified as a potential predictor of two-year survival and therapeutic efficacy [45].…”
Section: Targeting Immunosuppression In Gbmmentioning
confidence: 99%
“…Jie and colleagues recently published data from a clinical trial demonstrating that treatment with autologous DC vaccine increases the circulating pool of T lymphocytes and the release of cytokines (IL-2, IL-12 and IFN-γ), thus suggesting that vaccines can cultivate an immune profile favorable to combating tumor growth [39]. Notably, patients receiving vaccine also had improved tumor control rates, higher quality of life and prolonged survival [39]. More direct efforts to treat with IL-2 supplementation have further highlighted the importance of IL-2 in mounting an immune response against glioma [40].…”
Section: Pi3k Pathway Inhibitors and Interleukinsmentioning
confidence: 99%